The Scales That Limit: The Physical Boundaries of Evolution - Kempes, Christopher P.; Koehl, M. A. R.; West, Geoffrey B. (Frontiers in Ecology and Evolution, 2019)
Organisms are subject to the laws of physics, so the process of evolution by genetic variation and natural selection is constrained by these fundamental laws. Classic and recent studies of the biophysical limits facing organisms have shown how fundamental physical constraints can be used to predict broad-scale relationships between body size and organismal biomechanics and physiology. These relationships often take the form of power laws across a wide range of body sizes for organisms sharing a common body plan. However, such biophysical perspectives have not been fully connected with the detailed dynamics of evolution by natural selection, nor with the variation between species around the central scaling relationships. Here we first discuss what a general biophysical theory of evolution would require and provide an abstracted framework for aspects of such a theory. We discuss how such a theory should eventually be capable of not only predicting scaling relationships, but also of identifying the types of tradeoffs shown by different species occupying a particular niche. We then discuss how one key higher-order requirement of a biophysical theory of evolution is the ability to predict asymptotic behavior and the limits of a particular body plan. We use several examples to illustrate how dominant physical constraints can be used to predict the minimum and maximum body sizes for a particular body plan, and we argue that prediction of these limits is essential for identifying the dominant physical constraints for a given category of organisms. Our framework proposes that a major portion of fitness should be the overlay of how all traits of a particular body plan interact with fundamental physical constraints. In our examples we investigate multiple physical limits on particular traits, and also how the interaction of a number of traits determines the size limits on entire body plans, such as those of vascular plants. We use bacteria as an example of the shifts in which traits are most limiting at various sizes. Finally, we address the effects of environmental conditions and ecological interactions in determining which of the physical constraints faced by organisms are most likely to affect their fitness.